2020
DOI: 10.1002/cam4.3227
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of eflapegrastim to pegfilgrastim in the management of chemotherapy‐induced neutropenia in patients with early‐stage breast cancer undergoing cytotoxic chemotherapy (RECOVER): A Phase 3 study

Abstract: Eflapegrastim (Rolontis®) is a novel, long‐acting hematopoietic growth factor consisting of a recombinant human granulocyte‐colony stimulating factor (rhG‐CSF) analog conjugated to a human IgG4 Fc fragment via a short polyethylene glycol linker. We report results from a second pivotal, randomized, open‐label, Phase 3 study comparing the efficacy and safety of eflapegrastim to pegfilgrastim for reducing the risk of chemotherapy‐induced neutropenia. Patients with Stage I to IIIA early‐stage breast cancer (ESBC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In the phase 3 ADVANCE and RECOVER studies, the response to therapy, that is, mean duration of severe neutropenia, did not vary as a function of body weight for eflapegrastim and pegfilgrastim, ranging over the observed weights from 0.16 to 0.38 days and from 0.15 to 0.55 days, respectively. 13,14…”
Section: Pharmacodynamic Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the phase 3 ADVANCE and RECOVER studies, the response to therapy, that is, mean duration of severe neutropenia, did not vary as a function of body weight for eflapegrastim and pegfilgrastim, ranging over the observed weights from 0.16 to 0.38 days and from 0.15 to 0.55 days, respectively. 13,14…”
Section: Pharmacodynamic Resultsmentioning
confidence: 99%
“…Results from 2 phase 3 studies clearly showed that patient weight did not affect efficacy. 13,14 The wide range of weights (ie, 40-170 kg) provides a rich database to confirm that patients will be appropriately dosed by a fixed eflapegrastim dose of 13.2 mg (3.6 mg G-CSF), independent of body weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations